Influence of exogenously applied abscisic acid on carotenoid content and water uptake in flowers of the tea plant (Camellia sinensis). (14th November 2012) - Baldermann, Susanne; Yang, Ziyin; Sakai, Miwa; Fleischmann, Peter; Morita, Akio; Todoroki, Yasushi; Watanabe, Naoharu
Abstract: BACKGROUND: Carotenoids are a major class of plant pigments and fulfill many functions in different organisms that either produce or consume them. Although the color of the stamina of tea ( Camellia sinensis ) flowers is clearly due to the presence of carotenoids, the carotenoid profile and content remain to be discovered . RESULTS: We investigated the carotenoid profile of tea flowers and determined changes in concentrations over the floral development. The flowers contained oxygenated xanthophylls such as neoxanthin, lutein and zeaxanthin, as well as the hydrocarbons β‐carotene and α‐carotene. Flowers of the tea plant contain to vegetables comparable amounts of carotenoids. The content of 9′‐ cis ‐epoxycarotenoids, which serve as abscisic acid precursors, as well as changes in concentration of abscisic acid were studied. The concentrations of carotenoids decreased whereas the abscisic acid content increased over the floral development. Exogenously applied S ‐abscisic acid affected water uptake, flower opening and carotenoid accumulation . CONCLUSION: In summary, this paper reports, for the first time, the carotenoid profile and content of tea flowers. The study revealed that carotenoids in tea flowers are an interesting target in respect of possible applications of tea flower extracts as well as biological functions of abscisic acid during floral development. © 2012 Society of Chemical Industry